Functional Characterization of a LOV-Histidine Kinase Photoreceptor from Xanthomonas citri subsp. citri - Kraiselburd, Ivana (2015)
The blue-light (BL) absorbing protein Xcc-LOV from Xanthomonas citri subsp. citri is composed of a LOV-domain, a histidine kinase (HK) and a response regulator. Spectroscopic characterization of Xcc-LOV identified intermediates and kinetics of the protein's photocycle. Measurements of steady state and time-resolved fluorescence allowed determination of quantum yields for triplet (ΦT = 0.68 ± 0.03) and photoproduct formation (Φ390 = 0.46 ± 0.05). The lifetime for triplet decay was determined as τT = 2.4-2.8 μs. Fluorescence of tryptophan and tyrosine residues was unchanged upon light-to-dark conversion, emphasizing the absence of significant conformational changes. Photochemistry was blocked upon cysteine C76 (C76S) mutation, causing a seven-fold longer lifetime of the triplet state (τT = 16-18.5 μs). Optoacoustic spectroscopy yielded the energy content of the triplet state. Interestingly, Xcc-LOV did not undergo the volume contraction reported for other LOV domains within the observation time window, although the back-conversion into the dark state was accompanied by a volume expansion. A radioactivity-based enzyme function assay revealed a larger HK activity in the lit than in the dark state. The C76S mutant showed a still lower enzyme function, indicating the dark state activity being corrupted by a remaining portion of the long-lived lit state.